2021
DOI: 10.3389/fnbeh.2021.681593
|View full text |Cite
|
Sign up to set email alerts
|

Rest Is Required to Learn an Appetitively-Reinforced Operant Task in Drosophila

Abstract: Maladaptive operant conditioning contributes to development of neuropsychiatric disorders. Candidate genes have been identified that contribute to this maladaptive plasticity, but the neural basis of operant conditioning in genetic model organisms remains poorly understood. The fruit fly Drosophila melanogaster is a versatile genetic model organism that readily forms operant associations with punishment stimuli. However, operant conditioning with a food reward has not been demonstrated in flies, limiting the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…In a novel appetitive operant conditioning task flies were rewarded with sucrose when they turned in the desired direction on a Y-shaped track ( Wiggin et al, 2021 ). It was reported that only flies who rested during training (with rest defined as 1 min or more of continuous inactivity) were able to learn and perform well in this task.…”
Section: Memory Acquisition Is Impaired By Sleep Deprivationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a novel appetitive operant conditioning task flies were rewarded with sucrose when they turned in the desired direction on a Y-shaped track ( Wiggin et al, 2021 ). It was reported that only flies who rested during training (with rest defined as 1 min or more of continuous inactivity) were able to learn and perform well in this task.…”
Section: Memory Acquisition Is Impaired By Sleep Deprivationmentioning
confidence: 99%
“…It was reported that only flies who rested during training (with rest defined as 1 min or more of continuous inactivity) were able to learn and perform well in this task. Interestingly, and perhaps counter-intuitively, optogenetically inducing sleep via activation of the dorsal FB did not enhance learning ( Wiggin et al, 2021 ). This suggests that spontaneous rest is required to perform well but not sufficient to induce learning in this task, or that the specific restorative rest that gates learning in this operant task is driven by a different neural population.…”
Section: Memory Acquisition Is Impaired By Sleep Deprivationmentioning
confidence: 99%
See 2 more Smart Citations
“…To answer these questions, we designed an olfactory two-alternative forced choice (2AFC) task for individual Drosophila , inspired by earlier behavior assays for flies ( 57 61 ) and foraging related 2AFC tasks in vertebrates ( 10 12 , 14 ). The assay allows us to measure hundreds of sequential choices from individual flies as we vary the probability of reward associated with different odor cues.…”
mentioning
confidence: 99%